2016
DOI: 10.1155/2016/2605602
|View full text |Cite
|
Sign up to set email alerts
|

An Approach Based on the Exploratory Data Analysis to Relate the Wear Behavior with the Microstructure of Ductile Cast Irons

Abstract: The aim of this work is to propose a new methodology to relate Ductile Cast Irons (DCIs) wear behavior with the separation distances and sizes of the graphite nodules through an Exploratory Data Analysis (EDA). This methodology consists of morphological image processing tools (compacity and size distribution curves), an EDA performed by the use of box plots and an EDA-based section classifying algorithm. This algorithm classifies the microstructure of DCIs into classes and levels grouping different behaviors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…For the new enterprise financing investment risk subset, we need to optimize and perfect the traditional subset [ 6 ]. The selection of risk factors for financing investment of enterprises should be more dynamic and complicated, and should also be integrated into the characteristics of enterprises themselves [ 7 ]. If the selected indicators are not appropriate, the investment loss of enterprises will be caused, so each factor must be carefully screened.…”
Section: Evaluation Of Risk Factor Of Financing Investmentmentioning
confidence: 99%
“…For the new enterprise financing investment risk subset, we need to optimize and perfect the traditional subset [ 6 ]. The selection of risk factors for financing investment of enterprises should be more dynamic and complicated, and should also be integrated into the characteristics of enterprises themselves [ 7 ]. If the selected indicators are not appropriate, the investment loss of enterprises will be caused, so each factor must be carefully screened.…”
Section: Evaluation Of Risk Factor Of Financing Investmentmentioning
confidence: 99%
“…44 This study found patterns and provided insights that outputs of individual studies could not reveal. Another example of utilizing EDA was on ductile cast irons focusing on the relationship between wear behavior and graphite characteristics 45 where findings were used for a predictive model and classification of automotive parts.…”
Section: Introductionmentioning
confidence: 99%
“…Nodul grafit & distribusi ukuran telah dianalisis TWDI, penghitungan nodul 2-D dikonversi menjadi jumlah nodul 3-D dengan metode FDM [21]. Metodologi baru berhubungan Ductile Iron Cast Irons (DCIS) memakai perilaku dengan jarak pemisahan & ukuran nodul grafit melalui analisis data eksplorasi [22]. Sama halnya parameter perlakuan panas sifat plastik unalloyed Ductile Iron ausferritic, seperti pemanjangan & ketangguhan suhu 60° C [23] [13].…”
unclassified